Bioremediation of drill cuttings from oil based muds - Turner, Katharine Patricia (2002)
Analytical techniques applicable to the assay and remediation of cutting/mud matrices have been developed, utilising soxhlet extraction with dichloromethane and a drying agent followed by analysis using Gas Chromatography (FID). Calibration curves of oil content were produced for Novatec and Versaplus coated cuttings that were also sized by wet and dry sieving techniques, demonstrating their variable nature. The oil in each size fraction was assessed and showed that the finer fractions preferentially adsorbed the oil. Bacteria were isolated from the cuttings, muds and the pure oils to see if any indigenous species could, with optimum conditions, remediate the oil they contained. The resulting isolates were batch-tested in the laboratory in a minimal medium, with the drill cuttings providing the sole carbon source. Each isolate was scored for remediation performance, with reduction in oil varying from 50% to 6% within one week. Subsequently three bacteria (A,D & J) were identified using 16SrRNA sequencing; they were Bacillus Thuringiensls (A&D) and a novel species related to Bacillus oleronius. These were then tested slurry-phase in a rotating drum bioreactor designed and fabricated for the research against a known remediator, Rhodococcus 9737, and a non-inoculated control for four weeks. All the reactors remediated, but Rhodococcus 9737 reduced the oil to 35% of the original, A, D and other isolates as a consortium to 83% and J, 90%. Further tests in the bioreactors, after a modification to improve the air supply gave reductions of around 50% after four weeks. The high clay content of the cuttings was detrimental to significant levels of bioremediation in a slurry-phase bioreactor. Manures were added to the drill cuttings and tested in the bioreactors as a solid-phase system. These degraded the cuttings oil to 2% (v/v), a 96% reduction. Composting was thus more applicable for a high clay content drilling waste bioremediation system.